Genomic signatures and co-occurrence patterns of the ultra-small Saccharimonadia (phylum CPR/Patescibacteria) suggest a symbiotic lifestyle - Lemos, Leandro N.; Medeiros, Julliane D.; Dini-Andreote, Francisco; Fernandes, Gabriel R.; Varani, Alessandro M. [UNESP]; Oliveira, Guilherme; Pylro, Victor S. (Wiley, 2019)
The size of bacterial genomes is often associated with organismal metabolic capabilities determining ecological breadth and lifestyle. The recently proposed Candidate Phyla Radiation (CPR)/Patescibacteria encompasses mostly unculturable bacterial taxa with relatively small genome sizes with potential for co-metabolism interdependencies. As yet, little is known about the ecology and evolution of CPR, particularly with respect to how they might interact with other taxa. Here, we reconstructed two novel genomes (namely, Candidatus Saccharibacter sossegus and Candidatus Chaer renensis) of taxa belonging to the class Saccharimonadia within the CPR/Patescibacteria using metagenomes obtained from acid mine drainage (AMD). By testing the hypothesis of genome streamlining or symbiotic lifestyle, our results revealed clear signatures of gene losses in these genomes, such as those associated with de novo biosynthesis of essential amino acids, nucleotides, fatty acids and cofactors. In addition, co-occurrence analysis provided evidence supporting potential symbioses of these organisms with Hydrotalea sp. in the AMD system. Together, our findings provide a better understanding of the ecology and evolution of CPR/Patescibacteria and highlight the importance of genome reconstruction for studying metabolic interdependencies between unculturable Saccharimonadia representatives.
Keywords: acid mine drainage; metagenome-assembled genome; Saccharimonadia; symbiosis